N. F. S. Grundtvig: Blik på poesiens historie og Bernhard Severin Ingemann. Udg. af Flemming Lundgreen-Nielsen - Albeck, Gustav (Grundtvig-studier, 1986)
N . F. S. Grundtvig: View of the History of Poetry and Bernhard Severin Ingemann. MS in the Grundtvig Archives, Fasc. 179, 1, from 1822.Edited by Flemming Lundgreen-Nielsen. Museum Tusculanum, Copenhagen 1985.Reviewed by Gustav Albeck. This is a manuscript that deserves to have been edited and published before now. The poet’s son, Svend Grundtvig, did the preparatory work but never got his edition published. The cover of the present edition depicts W. E. Parry’s two ships in the polar darkness during his attempt to discover the North-West Passage in 1819-20. The reviewer informs us that in the manuscript Grundtvig describes the development of poetry as an unbroken chain of voyages of discovery, in which the contemporary, unsolved problem of the North-West Passage appears as a recurrent metaphor in various contexts.The editor, the excellent Grundtvig scholar, Dr. Lundgreen-Nielsen, has supplied a compact and scholarly preface and a commentary that is almost too thorough. Yet it must be admitted that the text requires both empathy and notes. It is not easy tofollow the poet’s image-filled presentation. It has previously been employed by Fr. R.nning in a little piece on Grundtvig as an aesthete (1883) and in the anthology Towards a Characterisation of N . F. S. Grundtvig (1915). Dr Alf Henriques has advanced some important reflections on this in his doctorate Shakespeare and Denmark (1941), as has Dr Helge Toldberg in his doctorate Grundtvig’s Symbolism (1950). Most recently Helge Grell has made use of some of the views expressed therein in his book The Creative Word and the Figurative Word (1980).The text is an interesting link in the development of Grundtvig’s view of the nature and mission of poetry. It does not tell us much about the poet Ingemann, even though it is evident from the manuscript that his name was the original title; comment on him fills a mere eight of the manuscript’s forty pages. In a kind of epilogue Grundtvig himself recognises that the essay assumes a knowledge of “the poetry and achievements of the strangest peoples” and the ability to “gather what they know”, an art which is far from common. But it is the hope of both editor and reviewer that it will find a varied group of readers.The introduction offers an outline of Grundtvig as an aesthete, a full and stimulating contribution to a work that is still waiting to be written. It does demand, however, “a systematic publication of the posthumous papers concerned with aesthetic matters,” and “a special Grundtvig dictionary”: two wishes that the reviewer shares with the editor. But there are other areas where Professor Albeck disagrees with, and is critical of, Dr Lundgreen-Nielsen.For example, the reviewer does not believe the essays were written with foreigners in mind. In his epilogue Grundtvig writes that here he “had strangers in mind” (nb. the Danish word fremmed means both ‘strange’ and ‘foreign’). The question is, What does he mean by ‘strangers’? Both the content and the language point to him addressing a domestic audience, but one that is distanced from him. He presupposes an acquaintance with the Danish language and history as well as a love of Denmark that could scarcely be expected of any but his compatriots. It is possible that originally he did have a foreign audience in mind, but changes his direction. Professor Albeck imagines that Grundtvig has originally thought of a Danish periodical (or possibly the Danish newspaper Latest Pictures of Copenhagen, where he has found one of the essay’s main images, the North-West Passage). The title suggests that Grundtvig’s primary interest has been to introduce his poet-friend Ingemann to a wider public, but that the introduction to this has swollen out of all proportion into a strongly subjective survey of the history of poetry in the world.